Studi Geologi dan Logam Tanah Jarang (RE) Daerah Air Gegas, Bangka Selatan - Soetopo, Bambang (BRIN Publishing, 2013)
Rare Earth (RE) is a valuable commodity both for industry and for the Nuclear Power Plant (NPP). In RE chemical bonds present in the phosphate (P) are the mineral monazite, xenotime, zircon minerals associated with cassiterite, magnetite, ilmenite, rutile, anatase, apatite, quartz and feldspar sand deposits are found in alluvial river or beach placer. RE deposits in monazite, zircon, xenotime in the Air Gegas of South Bangka area is an alluvial river that has the ease of exploration and mining. Geologically, monazite, xenotime and zircon minerals are from Klabat Granite aged Jurassic. The used method are the observation of geology, radioactivity measurement, sampling, laboratory analysis (microscopic and XRF). Results showed that the geology of the area Air Gegas of Tanjung Genting Formation consists of sandstone, clay (Early Triassic), Klabat Granite (Late Jurassic-Early Triassic) and Alluvial sediments (Quaternary). Alluvial monazite containing 0.071 to 3.574%, zircon from 0.172 to 10.376%, xenotime from 0.15 to 3.023% of the weight of MB from 10.73 to 168.072 grams. The presence of rare earth (RE) metals is derived from the mineral monazite, xenotime, zircon that was derived from granitic rocks of Klabat. Rare earth (RE) distributed in the eastern part of the study area which occupies the valley of the river.